Cephalosporins-induced intestinal dysbiosis exacerbated pulmonary endothelial barrier disruption in streptococcus pneumoniae-infected mice - Wang, Jia-Feng; Shi, Chang-Yi; Ying, Hua-Zhong (Frontiers in Cellular and Infection Microbiology, 2022)
Antibiotic abuse is growing more severe in clinic, and even short-term antibiotic treatment can cause long-term gut dysbiosis, which may promote the development and aggravation of diseases. Cephalosporins as the broad-spectrum antibiotics are widely used for prevention and treatment of community-acquired respiratory tract infection in children. However, their potential consequences in health and disease have not been fully elaborated. In this study, the effects of cefaclor, cefdinir and cefixime on intestinal microbiota and lung injury were investigated in Streptococcus pneumoniae (Spn)-infected mice. The results showed that the proportion of coccus and bacillus in intestinal microbiota were changed after oral administration with cefaclor, cefdinir and cefixime twice for 10 days, respectively. Compared with the Spn-infected group, the proportion of Bifidobacterium and Lactobacillus in intestine were significantly reduced, while Enterococcus and Candida was increased after cephalosporin treatment. Furthermore, 3 cephalosporins could obviously increase the number of total cells, neutrophils and lymphocytes in BALF as well as the serum levels of endotoxin, IL-2, IL-1β, IL-6 and TNF-α. Mechanically, cephalosporins accelerated Spn-induced pulmonary barrier dysfunction via mediating the mRNA expressions of endothelial barrier-related proteins (Claudin 5, Occludin, and ZO-1) and inflammation-related proteins (TLR4, p38 and NF-κB). However, all of those consequences could be partly reversed by Bifidobacterium bifidum treatment, which was closely related to the elevated acetate production, indicating the protective effects of probiotic against antibiotic-induced intestinal dysbiosis. Therefore, the present study demonstrated that oral administration with cephalosporins not only disrupted intestinal microecological homeostasis, but also increased the risk of Spn infection, resulting in severer respiratory inflammation and higher bacterial loads in mice.